Community Health Service in Tuberculosis Cases in the Lawawoi Health Center Working Area - Sellan, Rudolof Nino; Musiana, Musiana; Surasno, Diah Merdekawati; Nuryani, Siti; Tondok, Santalia Banne; Marjuannah, Marjuannah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Tuberculosis is a directly infectious disease caused by tuberculosis germs, namely Myobacterium Tuberculosis. The majority of tuberculosis germs attack the lungs, but tuberculosis germs can also attack other body organs. Tuberculosis is a direct infectious disease caused by tuberculosis germs (Mycobacterium Tuberculosis). The aim of this research is to determine factors related to the role as a tuberculosis program officer in tuberculosis cases in the Lawawoi Community Health Center work area. This research method uses an analytical research design, which is research to find out how and why a phenomenon occurs through statistical analysis such as the correlation between cause and effect or risk factors and effects and then it can be continued to find out how big the contribution of the cause or risk factor is to the effect. or effect. The results of this research show that good training with the role of a tuberculosis program officer is good at (23.7%) for the discovery of tuberculosis cases in the work area of the Lawawoi health center, which means that training is very important because it is a method used by institutions such as the health center in Lawawoi to maintain and safeguard, maintain the competence of tuberculosis program officers in finding tuberculosis cases. The research conclusion is that there is a relationship between training and the role as a tuberculosis program officer on the discovery of tuberculosis cases in the working area of the Lawawoi Community Health Center. Significant Value 0.000<0.05. There is a relationship between attitudes and the role as a tuberculosis program officer towards finding tuberculosis cases in the Lawawoi Community Health Center working area. Significant Value 0.006<0.05. There is a relationship between motivation and the role as a tuberculosis program officer on the discovery of tuberculosis cases in the working area of the Lawawoi Community Health Center. Significant Value 0.001<0.05.